In-Situ Iodine Doping Characteristics of Conductive Polyaniline Film Polymerized by Low-Voltage-Driven Atmospheric Pressure Plasma - Kim, Jae Yong (Polymers (Basel), 2021)
In-situ iodine (I(2))-doped atmospheric pressure (AP) plasma polymerization is proposed, based on a newly designed AP plasma reactor with a single wire electrode that enables low-voltage-driven plasma polymerization. The proposed AP plasma reactor can proceed plasma polymerization at low voltage levels, thereby enabling an effective in-situ I(2) doping process by maintaining a stable glow discharge state even if the applied voltage increases due to the use of a discharge gas containing a large amount of monomer vapors and doping materials. The results of field-emission scanning electron microscopy (FE-SEM) and Fourier transformation infrared spectroscopy (FT-IR) show that the polyaniline (PANI) films are successfully deposited on the silicon (Si) substrates, and that the crosslinking pattern of the synthesized nanoparticles is predominantly vertically aligned. In addition, the in-situ I(2)-doped PANI film fabricated by the proposed AP plasma reactor exhibits excellent electrical resistance without electrical aging behavior. The developed AP plasma reactor proposed in this study is more advantageous for the polymerization and in-situ I(2) doping of conductive polymer films than the existing AP plasma reactor with a dielectric barrier.